Ler o político no modo como se lê as metáforas de leitura no discurso da crítica literária - Bicicgo, Cleber (2014)
From the concept of metaphor and metaphorical effect’snotion based on Michel Pêcheux’swork, this dissertation proposes to examine the metaphors of reading on the discourse of literary criticism to understand the functioning of the political-ideological discourse in metaphorical discourse. The ideological struggle in the production of knowledge, according to Pêcheux, is the materiality of metaphor that a science uses “to understand and be understood”.So, questioning the metaphors of reading, as they are formulated in the discourse of literary criticism, this study leads to the conclusion that historical and discursive constitution of metaphors does not have a source, but different ways of working, conjuncturally taken by the dispute between different conceptions of reading. Based on this understanding, two considerations arise: the first is that there is no homogeneous memory that would be the “origin” of metaphor; the second is that the metaphor is produced according to the context of production and can move within different discursive formations. The functioning of metaphoric discourse marks a political-ideological stance which the results points to the relationship between scientific practice and political practice, embodied in the metaphors of reading. It is, thus, a study that discusses the metaphoric discourse from the political-ideological stance that the literary critic subject assumes when he interprets. This research makes an important contribution to studies on metaphor, from the perspective of discourse analysis, in addition to supporting the literary criticism itself on understanding the historical process that marks the metaphors it uses to understand the functioning of the senses in a literary work.